Effect of Moderate Exercise Training on Diabetic Status and Pancreatic Insulin Content in Diabetic Rats - Traisaeng, Supitchaya; Sanguanrungsirikul, Sompol; Keelawat, Somboon; Somboonwong, Juraiporn (Journal of Physiological and Biomedical Sciences, 2014)
Moderate-intensity exercise training appears to produce more positive impact for diabetic patients than low- or high-intensity exercise training. However, information regarding its effect on insulin content in pancreatic islets is still limited. The objective of this study was to examine the effect of moderate exercise training on pancreatic insulin content and diabetic status in streptozotocin-induced diabetic rats. Twenty four male Wistar rats were randomly divided into three groups with 8 animals per group as follows: 1) sedentary non-diabetic control group (CON), 2) sedentary diabetic group (DM), and 3) exercise-trained diabetic group (DME). The rats in DME group were engaged in moderate exercise training program that involved 30-min exercise on a treadmill at 18 m/min once daily, 5 days per week for 6 weeks. Bodyweight (BW) was recorded weekly. After 6-week experimental period, levels of fasting plasma glucose (FPG), plasma insulin, serum fructosamine, as well as islet size and density, and pancreatic insulin content were determined. The results showed that DME exhibited a significant decrease in FPG levels and an improvement in BW compared to DM. The levels of serum fructosamine and plasma insulin in DME were not different from those of DM. The density of pancreatic islets in DM and DME was reduced compared to that of CON. Islet diameter of DME tended to be greater than that of DM but was comparable to CON. Insulin content per islet and per beta cell in DME was higher than that of DM. Compared to CON, DME had a higher insulin content per beta cell despite a lower insulin content per islet. In conclusion, moderate exercise training improves diabetic status and increases pancreatic insulin content in type 1 diabetic rat model.